Online Participation and the New Global Democracy: Avaaz, a Case Study - Horstink, Lanka (2016)
More than 20 years after the Earth Summit of 1992, which introduced important social and ecological principles for policy-making and institutionalised participation, citizens are still largely excluded from decision-making processes that affect them. The internet was expected to change the balance of power in global politics. It has provided a platform for the presentation of alternative discourses and facilitated the organisation of social movements that clamour for a voice in global decision-making. The recent phenomenon of digital mobilisation has enthused the media, politicians, scholars and internet users alike. Could this be global democracy in the making? This article takes a critical look at the current dynamics of online participation, in particular the recent trend of online mass mobilisation, and will analyse the discourse, claims and practices of the web’s largest movement, Avaaz, in an attempt to assess the democratic quality of an organisation that insists it is “people-powered” and “member-driven”.